Diet composition of wild columbiform birds: next-generation sequencing of plant and metazoan DNA in faecal samples - Schumm, Yvonne R.; Masello, Juan F.; Vreugdenhil-Rowlands, Jennifer; Fischer, Dominik; Hillerich, Klaus; Quillfeldt, Petra; Justus Liebig University Giessen (My University, 2023)
Accurate knowledge of a species’ diets is fundamental to understand their ecological requirements. Next-generation sequencing technology has become a powerful and non-invasive tool for diet reconstruction through DNA metabarcoding. Here, we applied those methods on faecal samples of Common Woodpigeons Columba palumbus, European Turtle Doves Streptopelia turtur, and Stock Doves C. oenas to investigate their dietary composition. By applying primer pairs targeting both the ITS2 region of plant nuclear DNA and the mitochondrial COI region of metazoan DNA, we provide a complete picture of the food ingested and estimate the dietary overlap between the columbiform species during the breeding season. Animal DNA was present very rarely, and a diverse range of plants from the class Spermatopsida dominated the diet, with Asteraceae, Brassicaceae, Cucurbitaceae, Fabaceae, and Poaceae as the most frequently represented families. Generally, we detected a variability between species but also amongst individual samples. Plant species already known from previous studies, mainly visual analyses, could be confirmed for our individuals sampled in Germany and the Netherlands. Our molecular approach revealed new plant taxa, e.g. plants of the families Malvaceae for Woodpigeons, Lythraceae for Turtle Doves, and Pinaceae for Stock Doves, not found in previous studies using visual analyses. Although most of the plant species observed were of wild origin, the majority of cultivated plants found were present in higher frequencies of occurrence, suggesting that cultivated food items likely constitute an important part of the diet of the studied species. For Turtle Doves, a comparison with previous studies suggested regional differences, and that food items (historically) considered as important part of their diet, such as Fumitory Fumaria sp. and Chickweed Stellaria media, were missing in our samples. This indicates that regional variations as well as historic and current data on diet should be considered to plan tailored seed mixtures, which are currently proposed as an important management measure for conservation of the rapidly declining Turtle Dove.
Keywords: ddc:570; ddc:590